Outcomes of endovascular thrombectomy in patients selected by computed tomography perfusion imaging – a matched cohort study comparing nonagenarians to younger patients. (2nd September 2021) - Rahangdale, Rahul; Hackett, Christopher Todd; Cerejo, Russell; Fuller, Nicholas M; Malhotra, Konark; Williamson, Richard; Hentosz, Terry; Tayal, Ashis H; Rana, Sandeep S
Abstract : Background: Endovascular thrombectomy (EVT) is efficacious for appropriately selected patients with large vessel occlusions (LVO) up to 24 hours from symptom onset. There is limited information on outcomes of nonagenarians, selected with computed tomography perfusion (CTP) imaging. Methods: We retrospectively analyzed data from a large academic hospital between December 2017 and October 2019. Patients receiving EVT for anterior circulation LVO were stratified into nonagenarian (≥90 years) and younger (<90 years) groups. We performed propensity score matching on 18 covariates. In the matched cohort we compared: primary outcome of inpatient mortality and secondary outcomes of successful reperfusion (TICI ≥2B), symptomatic intracranial hemorrhage (sICH), and functional independence. Subgroup analysis compared CTP predicted core volumes in nonagenarians with outcomes. Results: Overall, 214 consecutive patients (26 nonagenarians, 188 younger) underwent EVT. Nonagenarians were aged 92.8±2.9 years and younger patients were 74.5±13.5 years. Mortality rate was significantly greater in nonagenarians compared with younger patients (43.5% vs 10.4%, OR 9.33, 95% CI 2.88 to 47.97, P<0.0001) and a greater proportion of nonagenarians developed sICH (13.0% vs 3.0%, OR 6.00, 95% CI 1.34 to 55.20, P=0.02). There were no significant differences for successful reperfusion (P=1.00) or functional independence (P=0.75). Nonagenarians selected with smaller ischemic core volumes had decreased mortality rates (P=0.045). Conclusions: Nonagenarians were noted to have greater mortality and sICH rates following EVT compared with matched younger patients, which may be ameliorated by selecting patients with smaller CTP core volumes. Nonagenarians undergoing EVT had similar rates of successful reperfusion and functional independence compared with the younger cohort.